Representasi Cinta Tokoh Indar dalam Novel Bukan Cinta Monyet Karya Purnama Teduh: Perspektif Erich Fromm - Salwa Sabila (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to describe the representation of love in the character of Indar in the novel Bukan Cinta Monyet by Purnama Teduh based on Erich Fromm’s perspective. This study employs a descriptive qualitative method using a literary psychology approach. The source of this study is the novel Bukan Cinta Monyet, with data consisting of narrative quotations and dialogues related to the representation of love in the character of Indar. Data collection was conducted through reading and note-taking. Data analysis in this study employed content analysis, which includes data reduction, data presentation, and drawing conclusions. The results indicate that Indar’s representation of love, viewed from the perspective of existential needs, encompasses only the needs for relatedness and attachment. Indar’s representation of love demonstrates an orientation toward brotherly love and erotic love. Meanwhile, elements of mature love such as responsibility, care, respect, and knowledge have not been fully realized. Thus, Indar’s representation of love does not yet demonstrate the maturity of love, but rather the consistency of feelings she maintains from adolescence into adulthood.